Dietary nitrate augments muscle metabolic adaptation to high-intensity interval training - Thompson, C.; Bailey, S. J.; Blackwell, J. R.; Fulford, J.; Wylie, L. J.; Black, M. I.; Kelly, J.; McDonagh, S. T. J.; Carter, J.; Vanhatalo, A.; Jones, A. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Short-term dietary nitrate supplementation may favourably impact the intrinsic properties of skeletal muscle. It is unclear whether longer periods of nitrate supplementation may more favourably alter the physiological response to exercise and improve exercise performance. Furthermore, the possible interaction of a high-nitrate dietary supplement, such as beetroot juice (BR), with the adaptations to exercise training is presently unknown. We therefore tested the hypothesis that chronic BR supplementation would augment skeletal muscle metabolic adaptations to high-intensity interval training (HIIT). Twenty-four men and 24 women completed a series of exercise tests before and following a 4 week period in which they were assigned to: 1) HIIT and no supplementation (HIIT); 2) HIIT and nitrate-depleted beetroot juice as a placebo (HIIT+PL); 3) HIIT and nitrate-rich beetroot juice (~13mmol nitrate/day; HIIT+BR); or 4) no training and nitraterich beetroot juice (NT+BR). During sub-maximal exercise, V O2 was reduced by HIIT+BR and NT+BR but not HIIT or HIIT+PL. During incremental exercise, V O2peak was increased by HIIT and HIIT+BR but not HIIT+PL or NT+BR. Compared to pre-intervention, maximal citrate synthase activity was elevated in HIIT+BR only (Pre 15.9 ± 3.4 vs Post 18.1 ± 2.0 mol·g d/w/min; P<0.05). Similarly, muscle [glycogen] was higher (Pre 335 ± 119 vs Post 441 ± 144 mmol·kg d.w.-1; P<0.05), muscle pH was greater (Pre 6.9 ± 0.3 vs Post 7.1 ± 0.2; P<0.05) and [lactate] was lower in muscle (Pre 53 ± 33 vs Post 33 ± 26 mmol·kg d/w; P<0.05) and blood (Pre 5.0 ± 0.8 vs Post 3.7 ± 1.0 mM; P<0.05) at 3-min of severe-intensity exercise in HIIT+BR but not HIIT, HIIT+PL or NT+BR. However, the improvement in severe-intensity exercise performance was not different between training interventions. In conclusion, BR ingestion reduced the O2 cost of moderate-intensity exercise and increased peak WR during incremental exercise whereas HIIT improved V O2peak, peak WR, and severe-intensity exercise performance. Similar effects to HIIT alone and NT+BR were found when HIIT and BR were combined but, in addition, maximal CS activity was increased and muscle metabolic perturbation during severe-intensity exercise was reduced. These data indicate that the independent physiological stimuli provided by HIIT and BR may be additive. Dietary nitrate supplementation in the form of BR may potentiate muscle metabolic adaptations to HIIT.